Analisis Pelatihan Karyawan dan Kualitas Pelayanan Pada Café Diagram Di Kabupaten Bandung: Bahasa Indonesia - Syakira, Nayla; Junipriansa, Donni; Rahma, Dinda (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to analyze the effect of employee training on service quality at Café Diagram, Bandung City. The method used is a qualitative approach with phenomenological techniques, which involves in-depth interviews and direct observation. The research results show that employee training contributes to increased knowledge and skills, more proactive attitude changes, and increased customer satisfaction. Trained employees are able to provide better service, thus having a positive impact on customer loyalty. These findings emphasize the importance of management in designing sustainable training programs to improve service quality and operational effectiveness in the food and beverage industry.